Inelastic nuclear scattering of strongly absorbed particles - Potgieter, Johannes Matthys (Department of Physics, 2016)
Closed expressions for differential cross sections are derived from the Austern-Blair theory of inelastic nuclear scattering. These formulae are an extension of the strong absorption model of Frahn and Venter for elastic scattering. AU the well-known features of inelastic angular distributions of composite particles are shown explicitly. These include effects of the multipolarity of the transition, the nuclear interaction, the Coulomb force and the shape of the reflection coefficients in angular momentum space. Analyses of representative sets of experimental data are presented. The results indicate that the Austern-Blair theory. ts remarkably successful in representing the shape of the angular distribution, but tends to underestimate the deformation parameter.